2017
DOI: 10.1038/s41598-017-13337-9
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Degeneration Protein 3 (RD3) in normal human tissues: Novel insights

Abstract: The 195-amino-acid-long human Retinal Degeneration Protein 3 (RD3) is critical in the regulation of guanylate cyclase (GC) signaling and photoreceptor cell survival. Recently, we identified significant loss of RD3 in high-risk neuroblastoma and the influential role of RD3 in tumor progression. However, the functional characterization of RD3 in tumor systems has been hampered by the dearth of information on its localization in normal tissue and by the lack of antibodies suitable for staining FFPE tissue, primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Guanylate kinase regulation by RD3 might not be restricted to photoreceptor cells ( Lavorgna et al, 2003 ; Azadi, 2013 ), since recent studies revealed that RD3 is also found in other tissue types like epithelial cells and is more ubiquitously expressed ( Aravindan et al, 2017 ). Additionally, the authors suggest a metastasis suppressor function for RD3 in neuroblastoma ( Khan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guanylate kinase regulation by RD3 might not be restricted to photoreceptor cells ( Lavorgna et al, 2003 ; Azadi, 2013 ), since recent studies revealed that RD3 is also found in other tissue types like epithelial cells and is more ubiquitously expressed ( Aravindan et al, 2017 ). Additionally, the authors suggest a metastasis suppressor function for RD3 in neuroblastoma ( Khan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are, however, in disagreement with a previous study showing that inactivation of both RD3 alleles in LCA12 patients does not correlate with extraocular symptoms ( Perrault et al, 2013 ). Recently, RD3 immunoreactivity was detected in normal human cell types, in particular in epithelial cells ( Aravindan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, beyond retinal localization and functions in retinal degeneration, the physiognomy and functions of RD3 are unknown. We were the first to define the distribution of constitutive RD3 expression and localization in healthy human tissues 28 . Although researchers reported RD3 co-localization with the tumor suppressor PML 34 , the functional significance of RD3 in cancer biology is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…All TMA construction, RD3 IHC, and positivity scoring was performed and quantified as discussed in our earlier studies 27,28 . Dissemination of tumors to vital organs in PD were assessed by a pathologist (ZY) utilizing H&E- and synaptophysin (marker for NB) -stained sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation